Tracer Diffusion of Cobalt in High-Entropy Alloys AlxFeNiCoCuCr - Nadutov, V.M.; Mazanko, V.F.; Makarenko, S.Yu. (Металлофизика и новейшие технологии, 2017)
The Co diffusion in the as-cast high-entropy alloys AlxFeNiCoCuCr (x = 1, 1.5, 1.8) is studied by means of the tracer-diffusion method using the ⁶⁰Cо isotope. As shown, the Co diffusion in the high-entropy alloys occurs by means of the vacancy mechanism and the diffusion coefficient decreases approximately in three times (from 3.21•10⁻¹⁶ to 0.98•10⁻¹⁶ m⁻¹⁶s⁻¹) with the increasing Al concentration. The decelerated Co diffusion is explained in terms of relatively large and negative enthalpy of mixing.